Mechanics of composite and multifunctional materials. Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics /: Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics. Volume 7 : ([2016]) - Unknown
No abstract available